Osiris: a platform for advertising agricultural machinery rentals - Tiadoro, Eduardo; Wendt, Reinaldo Zimmer; Muniz, Miguel A. Bastos; Fialho, Matheus; Basso, Fábio; Bernardino, Maicon (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2025)
Context: Agribusiness is a key pillar of the Brazilian economy, significantly contributing to national growth and wealth generation. This sector heavily relies on agricultural machinery technologies to enhance productivity and operational efficiency. Problem: The high costs of acquiring and maintaining agricultural machinery restrict access for small-scale farmers. Furthermore, idle equipment generates significant passive costs, creating an additional barrier to its efficient use. Solution: This study proposes a tool for advertising agricultural machinery rentals, grounded in the principles of the sharing economy. The platform connects equipment owners with idle machinery to renters in need of such resources. IS Theory: The study is based on the DeLone and McLean Information Systems Success Model, which highlights system quality, information quality, and user satisfaction as critical factors for success. Method: A qualitative heuristic evaluation approach was used, focusing on experts’ perceptions of the system prototype to identify usability barriers and opportunities for improvement. Summary of Results: Most usability issues were classified as low or moderate severity, suggesting they can be resolved without significantly impacting the user experience. Violations were most frequent in consistency, system visibility, and error prevention, highlighting areas for prioritized improvement. Contributions and Impact on IS Field: This study advances the Information Systems field by demonstrating how sharing economy principles can inform digital solutions for agribusiness. It validates the application of the DeLone and McLean model in rural contexts and offers insights for addressing usability challenges, fostering innovation and accessibility in agricultural systems.